Selected Contemporary Challenges of Ageing Policy 2017
DOI: 10.24917/9788380840911.4
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Employment Policies for Older Adults in the Czech Republic, Poland, and Slovakia

Abstract: Adults aged 65 and above comprise the fastest growing sector of the world's population. In the context of increasing numbers of older adults, employment policies have become a prominent issue. Governments recognize the importance of increasing participation in working age population and providing them with equal workplace opportunities. Yet, it appears that policies raising employment rates of older adults have become a slogan that governments use for election purposes, but the reality is different. In the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The research team observed the social context of education for older adults, their connection to working life, as well as the system and methods of education for older adults in the V4 countries (Kocianová et al, 2013). M. Leszko and B. Bugajska (2017) carried out another comparative study focused on comparing the policies of employment of older adults in Slovakia, the Czech Republic and Poland. Preparation of Europeans for retirement was the topic of research within the Erasmus+ project called BALL -Be Active Through Lifelong Learning (2015).…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…The research team observed the social context of education for older adults, their connection to working life, as well as the system and methods of education for older adults in the V4 countries (Kocianová et al, 2013). M. Leszko and B. Bugajska (2017) carried out another comparative study focused on comparing the policies of employment of older adults in Slovakia, the Czech Republic and Poland. Preparation of Europeans for retirement was the topic of research within the Erasmus+ project called BALL -Be Active Through Lifelong Learning (2015).…”
Section: Methodology Of Researchmentioning
confidence: 99%